System architecture development of programming languages source code digital library in FTMSK / Mohd Sahli Nordin - Nordin, Mohd Sahli (2005)
Since 1985 or late 80's, Faculty of Information System and Quantitative Science (FTMSK) in Universiti Teknologi MARA had offering studies on various types of computer programming languages. Nowadays, the programming languages evolve rapidly from the first-generation languages to high-level or fourth-generation languages and it moves parallel with computer technology improvement in Malaysia. Along the road, some students and lecturer have given their good effort on developing a lot of amazing programming codes. However, no effort was done to preserve all of these contribution and great work especially their names, achievements and glorious moments. Only some of them were able to inherit their works because of no platform or system yet in FTMSK that enables source code sharing and repository. Therefore, a suitable platform should be developed to create a big archive of source code repository in a digital library format to collect, share and organize programming source code within FTMSK community. So, students and lecturers will enjoy the benefit of source code sharing especially in object-oriented programming where reusability can reduce time to produce more effective programming source code and new higher quality product or version. The open source practice may increase cost effectiveness of programming languages studies in UiTM and bring a new change in the programming language arena in the near future. By using the concept of knowledge sharing community within the faculty and taking the advantage of open source, web technology and good knowledge base architecture, FTMSK could brings a new change in the way the student learn programming language especially in educational institution. The more important thing is the historical evolution of programming languages will not be forgotten in the future.